Sociodemographic profile of the elderly living with HIV/AIDS: a study in two services in the Região dos Lagos, Rio de Janeiro State, Brazil (Research, Society and Development, 2020)
This study aimed to analyze the sociodemographic profile of elderly people living with HIV/AIDS in two Sexually Transmitted Infections Services in the Região dos Lagos-RJ. Field research with a qualitative, descriptive-exploratory approach, with 30 elderly people registered in these services. The interviews were conducted through the application of a semi-structured form, containing open and closed questions. The data were treated through the formulation of spreadsheets and graphs in the Software Microsoft Office Excel 2010©, with simple and percentage frequency calculations, as well as comparisons of findings. The ethical-legal processes were respected, and the research was appreciated by the Ethics Committee of the Medical College of Antônio Pedro Hospital, according to opinion n. 3.013.119. The analysis of the sociodemographic profile of the participants resulted in a predominance of the female gender, mean age of 66 years, heterosexual, with low schooling, with incomes from 1 to 2 minimum wages, pardo/black race, Catholic religion, retirees, with more than 10 years of coexistence with HIV, widowed and divorced. Among the interviewees, there was participation of serodiscordant couples, outlining difficulties in condom adherence, to the detriment of those who affirmed cessation of post-diagnosis sexual activities. These difficulties of understanding and accepting condom use, among other influential factors in the exposure issue, such as racial and educational, together with the difficulty of society to glimpse them within the scope of vulnerability to sexually transmitted infections, make them more susceptible to HIV infection contraction and a late diagnosis of infection.